Hubungan Emosi Positif dengan Kepuasan Hidup Pada Lanjut Usia (LANSIA) di Kota Padang Provinsi Sumatera: The Relationship Between Positive Emotions and Life Satisfaction for the Elderly (ELDERLY) in Padang City, Sumatra Province - Fitra Yeni (Fakultas Keperawatan Universitas Andalas, 2013)
The aim of this study is to examine whether there was relation between positive emotion and life satisfaction of elderly people. The data was collected by using two measuring tools : positive emotion scale and life satisfaction scale. The samples of this study were 120 elderly people from 20 Public Health Center in Padang municipality. The sampling technique which is used is quota sampling by considering the criteria: 1) Listed as patients of Public Health Center on 2010; 2) Either male or female 3) Has background culture of Minangkabau; and 4) 60 years old or more. The collected data then was analyzed by using correlation analysis technique. Based on correlation test can be concluded that there was strength relation between positive emotion scale and life satisfaction of elderly people. (p=0,000;r=0,630).